Seasonal and spatial variability in surface p CO 2 and air–water CO 2 flux in the Chesapeake Bay - Baoshan Chen; Wei‐Jun Cai; Jean R. Brodeur; Najid Hussain; Jeremy M. Testa; Wenfei Ni; Qian Li (Limnology and Oceanography, 2020)
Interactions between riverine inputs, internal cycling, and oceanic exchange result in dynamic variations in the partial pressure of carbon dioxide ( p CO 2 ) in large estuaries. Here, we report the first bay‐wide, annual‐scale observations of surface p CO 2 and air–water CO 2 flux along the main stem of the Chesapeake Bay, revealing large annual variations in p CO 2 (43–3408 μ atm) and a spatial‐dependence of p CO 2 on internal and external drivers. The low salinity upper bay was a net source of CO 2 to the atmosphere (31.2 mmol m −2 d −1 ) supported by inputs of CO 2 ‐rich Susquehanna River water and the respiration of allochthonous organic matter, but part of this region was also characterized by low p CO 2 during spring and fall phytoplankton blooms. p CO 2 decreased downstream due to CO 2 ventilation supported by long water residence times, stratification, mixing with low p CO 2 water masses, and carbon removal by biological uptake. The mesohaline middle bay was a net CO 2 sink (−5.8 mmol m −2 d −1 ) and the polyhaline lower bay was nearly in equilibrium with the atmosphere (1.0 mmol m −2 d −1 ). Although the main stem of the bay was a weak CO 2 source (3.7 ± 3.3 × 10 9 mol C) during the dry hydrologic (calendar) year 2016, our observations showed higher river discharge could decrease CO 2 efflux. In contrast to many other estuaries worldwide that are strong sources of CO 2 to the atmosphere, the Chesapeake Bay and potentially other large estuaries are very weak CO 2 sources in dry years, and could even turn into a CO 2 sink in wet years.